Kinematics and Control of a Planar Cable Robot - Kapitány, Pálma; Lénárt, József (International Journal of Engineering and Management Sciences, 2019)
This paper deals with the kinematics and control of a planar cable robot [1], which is driven by four DC motors with gear. Cable robots are frequently used e.g., for the motion of cameras in sport halls and stadiums and also in high storage logistical systems [2]. Main goal of this research work is to design and build a test bench with low budget, which can model the motion of real life cable robots.